Three perspectives on the Sabbath - Francois P. Möller (In die Skriflig, 2019)
There is still confusion in theology and especially among members of the church concerning the fourth commandment and its observance. The following questions could be asked: What is the meaning of the Sabbath? What is the intention of rest on this day? Ought this commandment still be honoured like the other nine commandments of the Law? Does it still have any meaning for the church, or is Sunday a replacement for the Sabbath? The objective is to obtain greater clarity concerning the meaning, contents and application of the Sabbath as presented in both the Old and the New Testament. This is done from a dogmatic emphasis by dividing the Sabbath into three perspectives: The Creation Sabbath (God’s identification with it), the Covenant Sabbath (Israel’s identification with it), and the Atonement Sabbath (the church’s identification with it). This division does not assume three separate Sabbaths, but they are perspectives on the one Sabbath of God. The threefold perspective will contribute to a universal view on the Sabbath as presented in the creation narrative, the nation of Israel, and the church of the New Testament. This universal view is grounded in Christ who is the focal point, contents and connection between the three given perspectives. It is a Christocentric point of view that gives perception on the meaning, observance, application and message of the Sabbath for the church and every believer of our day.